Imaging biomarkers in oncology: Basics and application to MRI. Issue 1 (3rd July 2018) - Dregely, Isabel; Prezzi, Davide; Kelly‐Morland, Christian; Roccia, Elisa; Neji, Radhouene; Goh, Vicky
Abstract : Cancer remains a global killer alongside cardiovascular disease. A better understanding of cancer biology has transformed its management with an increasing emphasis on a personalized approach, so‐called "precision cancer medicine." Imaging has a key role to play in the management of cancer patients. Imaging biomarkers that objectively inform on tumor biology, the tumor environment, and tumor changes in response to an intervention complement genomic and molecular diagnostics. In this review we describe the key principles for imaging biomarker development and discuss the current status with respect to magnetic resonance imaging (MRI). Level of Evidence: 5 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2018;48:13–26.